Energy Saving Potential of a Battery-Assisted Fleet of Trolley Buses*. Issue 11 (2016) - Ritter, Andreas; Elbert, Philipp; Onder, Christopher
Abstract: This article investigates the opportunities of integrating battery-assisted trolley buses into a given trolley bus network in public transportation. In this new generation of vehicles, the diesel-powered auxiliary unit is replaced with a high-performance traction battery. On the one hand, the new vehicles can be operated without the overhead wire, while on the other hand the battery capacity improves the overall system efficiency. The energy saving potential is identified via simulation of a realistic trolley bus line including the optimization of the energy management strategy. The problem is formulated as a convex optimal control problem. The results show that up to 20% of energy can be saved, compared to the case with conventional trolley buses only.